PI3K/Akt/mTOR inhibitors in breast cancer - Joycelyn JX Lee (Cancer Biology & Medicine, 2015)
Activation of the phosphoinositide 3 kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway is common in breast cancer. There is preclinical data to support inhibition of the pathway, and phase I to Ⅲ trials involving inhibitors of the pathway have been or are being conducted in solid tumors and breast cancer. Everolimus, an mTOR inhibitor, is currently approved for the treatment of hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative breast cancer. In this review, we summarise the efficacy and toxicity findings from the randomised clinical trials, with simplified guidelines on the management of potential adverse effects. Education of healthcare professionals and patients is critical for safety and compliance. While there is some clinical evidence of activity of mTOR inhibition in HR-positive and HER2-positive breast cancers, the benefits may be more pronounced in selected subsets rather than in the overall population. Further development of predictive biomarkers will be useful in the selection of patients who will benefit from inhibition of the PI3K/Akt/mTOR (PAM) pathway.